2015
DOI: 10.1523/jneurosci.0855-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Hunger States Control the Directions of Synaptic Plasticity via Switching Cell Type-Specific Subunits of NMDA Receptors

Abstract: It remains largely unknown whether and how hunger states control activity-dependent synaptic plasticity, such as long-term potentiation (LTP) and long-term depression (LTD). We here report that both LTP and LTD of excitatory synaptic strength within the appetite control circuits residing in hypothalamic arcuate nucleus (ARC) behave in a manner of hunger states dependence and cell type specificity. For instance, we find that tetanic stimulation induces LTP at orexigenic agouti-related protein (AgRP) neurons in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Many pre-synaptic sources of glutamate contribute to excitatory activation of AgRP/NPY neurons to drive feeding behavior, such as paraventricular hypothalamic Pituitary Adenylate Cyclase Activating Polypeptide (PACAP) neurons and glutamatergic neurons in the dorsomedial hypothalamus (Krashes et al, 2014 ). Further, post-synaptic alterations facilitate glutamate receptor driven excitability under the fasted condition (Liu et al, 2012 ; Qi and Yang, 2015 ). Synaptic integration occurs in concert with fasting induced changes to intracellular signals of AgRP/NPY neurons, notably including activation of Protein Kinase A (PKA) in arcuate AgRP/NPY neurons (Shimizu-Albergine et al, 2001 ; Nakajima et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many pre-synaptic sources of glutamate contribute to excitatory activation of AgRP/NPY neurons to drive feeding behavior, such as paraventricular hypothalamic Pituitary Adenylate Cyclase Activating Polypeptide (PACAP) neurons and glutamatergic neurons in the dorsomedial hypothalamus (Krashes et al, 2014 ). Further, post-synaptic alterations facilitate glutamate receptor driven excitability under the fasted condition (Liu et al, 2012 ; Qi and Yang, 2015 ). Synaptic integration occurs in concert with fasting induced changes to intracellular signals of AgRP/NPY neurons, notably including activation of Protein Kinase A (PKA) in arcuate AgRP/NPY neurons (Shimizu-Albergine et al, 2001 ; Nakajima et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Xia et al showed that miR-384-3p inhibited retinal neovascularization during diabetic retinopathy [48]. KEEG analysis also revealed that the miRNAs of interest control activity-dependent synaptic plasticity, such as long-term potentiation (LTP) and LTD. Interestingly, several studies highlighted that energy state may control the LTP as well as LTD [49,50]. Particularly, a tetanic stimulation protocol induced LTD at POMC neurons in fed mice but weak LTP in food-deprived mice [50].…”
Section: Discussionmentioning
confidence: 99%
“…KEEG analysis also revealed that the miRNAs of interest control activity-dependent synaptic plasticity, such as long-term potentiation (LTP) and LTD. Interestingly, several studies highlighted that energy state may control the LTP as well as LTD [49,50]. Particularly, a tetanic stimulation protocol induced LTD at POMC neurons in fed mice but weak LTP in food-deprived mice [50]. Then, it is conceivable that miRNAs may be involved in the control of LTP and LTD in POMC neurons.…”
Section: Discussionmentioning
confidence: 99%
“…It is noted that, except the common LTDs (Yang, Zhang, Wang, Ruan & Chen, 2012a, 2012b and even the rare LTPs (Sadowski, Jones & Mellor, 2016) forming in hippocampus in SWS, the neuronal plasticity in the lower portion of the subcortical limbic structures, such as those reported in the hypothalamus (Nisikawa, Shimazoe, Shibata & Watanabe, 2002;Panatier, Gentles, Bourque & Oliet, 2006;Qi & Yang, 2015) and epithalamus (Park et al, 2017), may lie even beyond the influences from the forebrain delta slow waves, spindles and ripples in SWS, which deserves more investigations. Notably, the LTP in suprachiasmatic nucleus(SCN) can be induced with different conditions modulated by daynight cycle (Nisikawa, Shimazoe, Shibata & Watanabe, 2002), implicating that the SCN LTP may possibly occur in SWS.…”
Section: The Emotional Regulation Via Locus Coeruleus In Swsmentioning
confidence: 99%
“…More investigations are required to look for LTD and even LTP in amygdala, septum, cingulate cortex and so on other forebrain limbic structures during SWS. (3) The hippocampal LTD (Yang, Zhang, Wang, Ruan & Chen, 2012a, 2012b in SWS, as well as the neuronal plasticity in the hypothalamus (Nisikawa, Shimazoe, Shibata & Watanabe, 2002;Panatier, Gentles, Bourque & Oliet, 2006;Qi & Yang, 2015) and epithalamus (Park et al, 2017), may all be related to the upregulation of NA in LC by SWS, while more investigations are required to look for neuronal plasticity in the hypothalamus and epithalamus during SWS.…”
Section: Brief Perspectivesmentioning
confidence: 99%